1999
DOI: 10.1111/j.1528-1157.1999.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Changes in the Medial Temporal Region During Intracarotid Amobarbital Procedure by Use of SPECT

Abstract: Summary: Purpose: Because the main blood supply to the medial temporal region is through the posterior cerebral artery, the validity of the intracarotid amobarbital procedure (IAP) is still debated. To verify clinical validity of the IAP, we investigated changes in neuronal function in the medial temporal region during IAP.Methods: Brain single photon emission computed tomography (SPECT) was performed during IAP (IAP-SPECT) in 22 patients with temporal lobe epilepsy (TLE), and regional cerebral blood flow (rC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
7
1
Order By: Relevance
“…These data are consistent with findings from previous single photon emission computed tomography (SPECT) studies (Kim, Lee, Nam, Song, & Lee, 1999;Urbach et al, 1999;Jeffrey et al, 1991). These studies strongly suggest that (in the absence of a direct ''fetal'' origin of the PCA from the ICA) an amytal injection into the ICA does not perfuse most of the medial temporal lobe, including most of the hippocampus and its associated cortex, but does anesthetize other cortical regions including the frontal and parietal cortex.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data are consistent with findings from previous single photon emission computed tomography (SPECT) studies (Kim, Lee, Nam, Song, & Lee, 1999;Urbach et al, 1999;Jeffrey et al, 1991). These studies strongly suggest that (in the absence of a direct ''fetal'' origin of the PCA from the ICA) an amytal injection into the ICA does not perfuse most of the medial temporal lobe, including most of the hippocampus and its associated cortex, but does anesthetize other cortical regions including the frontal and parietal cortex.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a SPECT study by Kim et al (1999) revealed decreased regional cerebral blood flow in the posterior portion of the hippocampus following ICA amytal injections. The SPECT study further revealed infrequent delivery of amytal to this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain SPECT images acquired after injection of Tc-99m-HMPAO into the internal carotid artery (ICA) during the intracarotid amobarbital procedure in epilepsy patients (IAP SPECT) provided superior anatomical information on the blood flow distribution from the ICA. This procedure used to be performed preoperatively to predict postoperative memory and language deficit after unilateral temporal lobectomy, and yielded very fine data regarding internal carotid arterial supply in population [27,28]. IAP SPECT during Wada test in epilepsy patients enabled the development of probabilistic maps of the distribution of blood supply from the ICA while SPECT images were transformed into the MNI stereotaxic coordinate [26] (Fig.…”
Section: Probabilistic Map Of Vascular Territorymentioning
confidence: 99%
“…This procedure (the intracarotid amobarbital procedure [IAP], or “Wada” test) provides a more direct assessment of hippocampal function than is possible with traditional assessment of memory. Although a complete review of the controversies regarding the Wada test is beyond the scope of this brief review, numerous lines of evidence have emerged that support the validity of the IAP as a measure of hippocampal function, including a correlation of IAP memory performance with hippocampal EEG changes recorded following injection (9) and reduced metabolism following injection of amobarbital (10,11), as well as neuronal cell loss (12) determined from resected tissue.…”
Section: Introduction: Hippocampal Model Of Memory and Assessment Of mentioning
confidence: 99%